Interculturality in the university education. A qualitative study. - Leiva-Olivencia, Juan José (My University, 2018)
Intercultural training in the University is a necessity and a hope. A need, to the extent that must respond to the complex social and educational realities where the different cultural element is absolutely real and emerging. And, a hope, because while we educate for the respect and the promotion of intercultural we will be training teachers who will grow in future generations the seeds of peace and solidarity, and, therefore, much-needed positive values and fundamental for humanity. Therefore, in this work, we will present the results of the qualitative part of the process of research carried out in the context of the Faculty of Education Sciences of the University of Malaga during the years 2015, 2016 and 2017. The pedagogical practice of initial formation must ensure intercultural inclusion, through strategies of work that is involved to the cultural diversity present in the University classroom, in order to improve human interactions within the space training, and outside, to generate attitudes of cooperation and intercultural dialogue in university students, extending these attitudinal "ramifications" to society in general.
Keywords: Educación inclusiva; Intercultural education; Culture of the diversity; Inclusion; University context